Análise da prática docente em uma iniciativa educacional que integra teoria e prática em cenários do SUS - Lara, Ellys Marina de Oliveira (2014)
Considering the hypothesis which says that the person responsible for people education is also being educated and modified during the teaching and learning processes along with individuals this person is teaching, this investigation aims to identify how the lecturer-facilitators from the “Clinical Governance in Health Regions” specialization understood their educational practice. The facilitators were simultaneously teachers from the “Clinical Governance in Health Regions” specialization and students from the “Health Educational Processes” specialization. Both specializations were built through a partnership between the Health Ministry – MS – and the Sírio-Libanês Teaching and Research Institute – IEP/HSL, being developed during the years of 2011 and 2012 in 10 Brazilian regions, indicated by MS. The courses utilized a constructivist approach and were guided by active methods of teaching and learning. The investigation was based upon the research qualitative principles and utilized the lecturer-facilitators Conclusion Course Thesis as the main source of data analysis. Among the thesis, the facilitators’ educational practice was reported in reflective synthesis about their teaching and learning trajectory. In order to interpret the data a thematic content analysis was applied. Two analytical categories was considered: Educational Practice and Health Care Practice. From those two categories, three thematic was identified: (i) Health professionals’ challenges in graduation and post-graduation; (ii) Building new strategies and educational capacities; (iii) Dialoguing with Clinical Governance elements. The first and the second thematic link to the analytical category “Educational Practice” and the third is linked to the category “Health Care Practice”. A fourth thematic (iv) called “Personal Life Transformations” was linked to the empirical category “Personal Development”. The facilitators’ conclusion course thesis pointed towards the competency profile development proposed by the course, especially to the articulation among educational and heath care practices. Accordingly, the autonomy ideas and construction of new knowledge, from the expansion of listening, respecting others and be tolerant to diversity, permeated all of the thematic. The feelings of discovery, joy and satisfaction reported by the facilitators, associated to the recognition of their own practice transformation point to the educational initiatives power, which integrates theory and practice.